Creepy - Sensenbrenner, Lee (Drawn & Quarterly, 2022)
"In this picture book for grown-ups, sibling duo Keiler Roberts and Lee Sensenbrenner render a compelling--and downright creepy--modern fable about kids who are hooked on their digital devices. Creepy is the contemporary answer to the shocking tales of the Brothers Grimm and bedtime moral stories like the boy who cried wolf or the princess and the pea: in it, Roberts and Sensenbrenner provide a shrewd and comical commentary on the increasing digitization of childhood. Known for her award-winning autobiographical comics, Roberts's signature deadpan humor is on full display in these vibrantly painted pages."--